2002
DOI: 10.1034/j.1600-6143.2002.20404.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia in Renal Transplant Recipients

Abstract: Renal transplantation is a commonly performed curative procedure for end-stage renal disease. With the increase in renal allograft half-lives, attention is now being focused on cardiovascular morbidity and death in the renal transplant recipient (RTR) population. Among the more novel cardiovascular disease (CVD) risk factors for which this group is at risk is hyperhomocysteinemia. Hyperhomocysteinemia has been associated with an increased risk of CVD, although prospective randomized trials designed to prove ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 52 publications
2
33
0
Order By: Relevance
“…10,11,12 The observation of hyperhomocysteinemia in about half of our diabetic renal transplant recipients has also been reported by others. 13,14 Folic acid has been shown to lower homocysteine levels in several studies. 8,15,16 We did not observe any significant difference in the values of total antioxidant status in diabetics with end stage kidney disease, uncomplicated diabetes mellitus, stable renal allograft recipients and healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,12 The observation of hyperhomocysteinemia in about half of our diabetic renal transplant recipients has also been reported by others. 13,14 Folic acid has been shown to lower homocysteine levels in several studies. 8,15,16 We did not observe any significant difference in the values of total antioxidant status in diabetics with end stage kidney disease, uncomplicated diabetes mellitus, stable renal allograft recipients and healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CKD, there is an inverse relationship between plasma homocysteine and renal function, with the highest levels in patients requiring dialysis [43]. Some observational cohort studies have suggested that homocysteine levels might represent an independent risk factor for CVD in this population [44,45,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia/reperfusion injury is a result of decreased blood flow to the tissue followed by restoration of blood flow to the ischemic area. Hyperhomocysteinemia is a common clinical finding in patients with chronic kidney disease or acute renal failure (24). We have investigated the role of CBS in Hcy and H 2 S metabolism in a rat model with kidney ischemia/reperfusion (16,25,26).…”
mentioning
confidence: 99%